Gambaran Higiene Sanitasi Depot Air Minum Isi Ulang Di Wilayah Kerja Puskesmas Kecamatan Matraman Kota Jakarta Timur Tahun 2023 - Riyanto, Agus; Saputra, Atang; Pangestu; Windah Aprilia, Adila (CV. Multi Kreasi Media, 2024)
Depot Air Minum or abbreviated as DAM is an industrial company that treats raw water into drinking water and sells it directly to consumers in the form of bottled drinking water which is relatively cheaper and more affordable. The quality of water produced from refilling drinking water depots has recently deteriorated due to frequent problems such as refilling drinking water storage devices that do not have sterilizers, have low bactericidal efficiency, or distributors who do not know the quality of water, the type of raw water used, filling equipment, good drinking water storage tanks and their maintenance and treatment of treated water and lack of monitoring of filling drinking water storage tanks do not allow the quality of the filling water produced to meet the specified quality standards. The results of 20 drinking water depots that were observed, the number of drinking water depots that met the requirements for the bacteriological quality of drinking water (positive) and qualified for the quality of sanitary hygiene were 91.6% then the number of drinking water depots that met the requirements for bacteriological quality but did not qualify for the quality of drinking water sanitary hygiene quality was 8.33%. Then the number of drinking water depots that do not meet the requirements for bacteriological quality (negative) but meet the requirements for the quality of drinking water depot sanitation hygiene is 37.5% while drinking water depots that do not meet the requirements for bacteriological quality but do not meet the requirements for the quality of drinking water depot sanitation hygiene is 62.5%. To reduce the negative impact that can endanger the community as a result of drinking water depots that do not meet the requirements, researchers suggest that the state of sanitary hygiene in each drinking water depot be further improved, both in terms of the environment, equipment, handlers, and raw water.